ҚЎШМА ГАПЛАРГА ХОС ШАКЛ ВА МАЗМУН НОМУТАНОСИБЛИГИ (Scientific journal of the Fergana State University, 2023)
In this article the problems of imbalance between taxonomic and functional units of compound sentences are analysed.